Diseases of the poultry reproductive organs (Case study: Altai Region, Russia) - Sergey V. Fedotov; Sergey V. Akchyrin; Evgeniya S. Latynina (Caspian Journal of Environmental Sciences)
We carried out a complex research on the determination of pathogenesis and etiology of diseases of egg-forming organs in laying hens in conditions of industrial breeding. We considered pathologies of the reproductive system of laying hens within the framework of three main directions: prevention of reproductive system diseases, mechanisms of organism defense and pathomorphogenesis of reproductive system pathologies, etiological factors, and potential biomarkers of reproductive system pathology. Based on the characteristics of localization of the pathological focus with the clinical and anatomical findings and physiological processes in the genital organs of hens, we have described the folliculitis of the ovary, magnuit, metritis, and vaginitis of the oviduct as an independent nosological unit. Analysis of biochemical changes in the blood of clinically diseased hens, postmortem autopsy data and the results of morphological and histological studies, which allowed us to describe new diseases folliculitis of the ovary; magnuitis, metritis and vaginitis in the oviduct independent of the disease. Specialists in industrial poultry farming can use the results obtained for the timely prevention and therapy of egg-forming organ diseases in laying hens. The waste of laying hens from egg formation organ pathology on poultry farms in the region increased by 30% in all diseases of infectious etiology. Dysfunction of the chicken’s genital organs is mainly caused by disorders of feeding, housing, and veterinary care, with a significant intensification of production aimed at increasing egg production.